2013
DOI: 10.1111/1462-2920.12340
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐guided insights into the versatile metabolic capabilities of the mercaptosuccinate‐utilizing β‐proteobacterium Variovorax paradoxus strain B4

Abstract: Variovorax paradoxus B4 is able to utilize 2-mercaptosuccinate (MS) as sole carbon, sulfur and energy source. The whole genome of V. paradoxus B4 was sequenced, annotated and evaluated with special focus on genomic elements related to MS metabolism. The genome encodes two chromosomes harbouring 5 795 261 and 1 353 255 bp. A total of 6753 putative protein-coding sequences were identified. Based on the genome and in combination with results from previous studies, a putative pathway for the degradation of MS coul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 105 publications
(137 reference statements)
0
13
0
Order By: Relevance
“…Cells of A. mimigardefordensis strain DPN7 T and the deletion mutant A. mimigardefordensis DdctP Am were harvested in the early exponential growth phase (OD 600 between 0.8 and 1). Total RNA was obtained by RNA isolation using acidic water saturated phenol (AppliChem, Darmstadt, Germany) as described elsewhere (Brandt et al, 2014). RT-PCR was carried out using the Qiagen 'One Step RT-PCR' kit following the manufacturer's instructions.…”
Section: Reverse Transcription-pcr (Rt-pcr)mentioning
confidence: 99%
“…Cells of A. mimigardefordensis strain DPN7 T and the deletion mutant A. mimigardefordensis DdctP Am were harvested in the early exponential growth phase (OD 600 between 0.8 and 1). Total RNA was obtained by RNA isolation using acidic water saturated phenol (AppliChem, Darmstadt, Germany) as described elsewhere (Brandt et al, 2014). RT-PCR was carried out using the Qiagen 'One Step RT-PCR' kit following the manufacturer's instructions.…”
Section: Reverse Transcription-pcr (Rt-pcr)mentioning
confidence: 99%
“…Some bacterial strains have been determined to possess genes for the utilization of not only monosaccharides such as glucose, fructose and galactose but also disaccharides such as lactose, maltose and trehalose (Brandt et al . ). Therefore, we demonstrated that trehalose was utilized as a carbon source in BCNU 106.…”
Section: Resultsmentioning
confidence: 97%
“…The sequence similarity of CdoB to members of the 2-mercaptosuccinate dioxygenase (Msdo) subtree amounts to 30% identical amino acids for both putative Cdohomologous Msdos from the genus Advenella and to only 27% identical amino acids of the confirmed Msdo from V. paradoxus strain B4 (54,55). A multiple-sequence alignment illustrates the similarities and differences between all the above-mentioned Cdos (and homologues thereof) in detail (see Fig.…”
Section: Resultsmentioning
confidence: 99%